International control of tritium for nuclear nonproliferation and disarmament - Kalinowski, Martin (CRC Press, 2004)
Tritium is the neglected material in controlling the proliferation of nuclear weapons. It is used by all nuclear weapons states to increase the explosive yield of atomic bombs and at the same time to miniaturize them. However, this radioactive material has not yet been put under appropriate international control comparable to the nuclear safeguards applied for plutonium and uranium. A carefully designed tritium control would be beneficial both for non-proliferation of tritium as well as for reserving the nuclear arms race.
Keywords: Tritium.; Nuclear disarmament.; Nuclear nonproliferation.; elektronické knihy; electronic books